Dissection length-to-descending thoraco-abdominal aorta length ratio predicts abdominal aortic enlargement after thoracic endovascular aortic repair for type B aortic dissection involving the abdominal aorta. (15th October 2020) - Wang, Xinhao; Ge, Yangyang; Ge, Xiaohu; Miao, Jianhang; Fan, Weidong; Liu, Jie; Rong, Dan; Xue, Yan; Liu, Feng; Jia, Xin; Liu, Xiaoping; Guo, Wei
Abstract: OBJECTIVES: This study was performed to assess the association between the dissection length-to-descending thoraco-abdominal aorta length ratio (LLR) and abdominal aortic enlargement (AAE) (≥20% increase in total abdominal aortic volume) after thoracic endovascular aortic repair (TEVAR) in patients with type B aortic dissection. METHODS: We retrospectively analysed data from 184 consecutive patients with type B aortic dissection who underwent TEVAR from January 2011 to December 2016 at 4 hospitals as part of the Registry Of type B aortic dissection with Utility of STent graft study. Preoperative and postoperative computed tomography angiography images were reviewed to assess the LLR and AAE. Patients were stratified into tertiles according to the pre-TEVAR LLR: 0.7 to <1.0 ( n = 61), 1.0 to <1.2 ( n = 61) and 1.2 to <1.6 ( n = 62). The thoracic and abdominal aorta were divided by the celiac trunk. The cumulative incidence of AAE was estimated using the Kaplan–Meier method. A multivariable Cox proportional hazards model was used to assess the independent association between the preoperative LLR and the post-TEVAR risk of AAE. The nonlinear relationship between the LLR and the risk of post-TEVAR AAE was fitted by the restricted cubic smoothing spline, and the inflection point on the fitting curve was determined using a piecewise linear regression model. RESULTS: Baseline demographics, clinical features, preoperative anatomic characteristics and implanted devices were similarly distributed among the pre-TEVAR LLR tertile groups. At 24 months post-TEVAR, the estimated cumulative incidence of AAE significantly differed ( P < 0.01) by LLR tertile group: 0.10 [95% confidence interval (CI) 0.00–0.21], 0.65 (95% CI 0.45–0.78) and 0.67 (95% CI 0.40–0.82), respectively. The pre-TEVAR LLR was an independent predictor of post-TEVAR AAE [hazard ratio (per unit increase) 1.03, 95% CI 1.01–1.04] following a nonlinear relationship with an inflection point at LLR = 1.0. CONCLUSIONS: The risk of post-TEVAR AAE is highest when the length of the dissection is greater than or equal to the length of the descending aorta (LLR ≥ 1.0). Abstract : Thoracic endovascular aortic repair (TEVAR) is a first-line treatment for acute complicated Stanford type B aortic dissection (TBAD) [1].